Exploring of the Genus Coffea L. (1753) in North Maluku: a Preliminary Study for Coffee Database - Bahtiar Bahtiar; Suparman Suparman; M. Nasir Tamalene; Yusmar Yusuf; Slamet Hariyadi (JURNAL BIOEDUKASI, 2025)
Genus Coffea L. (1753), family Rubiaceae, is well known as coffee; it has 171 accepted species with many synonyms from around the world. Coffee is exotic plant in Indonesia that was imported by Dutch. Now, in North Maluku, coffee is one of the cultivated plants. This study formally reported for the first time the data for Coffea spp. in North Maluku. The exploration research was conducted from January to June 2023 and collected three accepted species and one variety of Coffea namely Coffea arabica L., C. canephora Pierre ex Froehner, C. liberica Bull. Ex Hiern, and C. liberica var. dewevrei (De Wild. & T. Durand) Lebrun. The second species and C. liberica var. dewevrei are more popular known as coffee Robusta and Excelsa respectively. All species are discovered as cultivated plants and spread in many places in North Maluku. The C. liberica var. dewevrei or excelsa coffee is only cultivated in Sula district. This publication also shares information about the location and comparison of every taxon.